The Migraine Tree: a shared tool for migraine information - Leroux, Elizabeth (Headache Medicine, 2020)
Migraine awareness is a critical step in minimizing the disease burden. The Migraine Tree is a web structure designed by a Canadian team to inform people living with migraine and give them the knowledge they need to understand their disease and make daily decisions. This article summarizes the reasons for the creation of the Migraine Tree, its design and underlying principles and proposes future collaborations for translation in other languages.